Factors Determining CEO Compensation in an Emerging Economy : Evidence from India - Pathak, Deepti; Chopra, Monika (Indian Journal of Finance, 2021)
Executive compensation has been a topic of great interest in the academics as well as in the corporate world due to a growing bent of firms towards corporate governance practices. The present research work examined the various firm specific characteristics that influence the components of CEO’s compensation in Indian firms. The study selected a sample of 123 publicly listed Indian firms across different sectors. The research identified the determinants of CEO compensation in an emerging economy, India using data from FY 2012–18, a period that witnessed various changes in the executive compensation structure post the implementation of Companies Act, 2013. A panel data regression of select variables indicated that in India, a firm’s performance with respect to its profitability affected the retirement benefits given to CEOs, while its leverage and size significantly affected CEO’s salary as well as total remuneration. In addition, we found that firm’s size had a significant relationship with bonus component, and contribution to provident fund for key executives. However, none of the variables except firm’s size were found to have a significant relationship with the perquisites paid to the CEOs. The study concluded by giving policy implications and suggestions about linking CEO compensation to profitability, stability, and sustainability of the organization.